Faded - Walker, Alan (Training Open Journal System LPPI UMS, 2018)
You were the shadow to my lightDid you feel usAnother startYou fade awayAfraid our aim is out of sightWanna see usAliveWhere are you nowWhere are you nowWhere are you nowWas it all in my fantasyWhere are you nowWere you only imaginaryWhere are you nowAtlantisUnder the seaUnder the seaWhere are you nowAnother dreamThe monsters running wild inside of me